Molecular dynamics study on the effect of temperature on HCP→FCC phase transition of magnesium alloy - Chun Xue; Shuai Li; Zhibing Chu; Qianhua Yang; Yugui Li; Lifeng Ma; Leifeng Tuo (Journal of Magnesium and Alloys, 2023)
To explore the effect of temperature on the phase transformation of HCP→FCC during compression, the uniaxial compression process of AZ31 magnesium alloy was simulated by the molecular dynamics method, and the changes of crystal structure and dislocation evolution were observed. The effects of temperature on mechanical properties, crystal structure, and dislocation evolution of magnesium alloy during compression were analyzed. It is concluded that some of the Shockley partial dislocation is related to FCC stacking faults. With the help of TEM characterization, the correctness of the correlation between some of the dislocations and FCC stacking faults is verified. Through the combination of simulation and experiment, this paper provides an idea for the in-depth study of the solid-phase transformation of magnesium alloys and provides reference and guidance for the design of magnesium alloys with good plasticity and formability at room temperature.